Evaluasi Usability pada Aplikasi OVO Menggunakan Metode System Usability Scale (SUS) - Hillal Al Rosyid; Diovianto Putra Rakhmadani; Shintia Dwi Alika (JURIKOM (Jurnal Riset Komputer), 2022)
In the current era of globalization, information technology is developing very rapidly. On the other hand, during this pandemic due to the impact of COVID-19, Fintech is also widely used, especially the OVO application and plays an important role in reducing the amount of spread of the COVID-19 virus because we don't have direct physical contact. Based on Neurosensum's research, he presented the results of digital research with a special study focusing on the use of e-wallets as a digital transaction medium for 1,000 active e-commerce user respondents of productive age (19-45 years) simultaneously in 8 major cities in Indonesia during November 2020 - January 2021. The results of the research stated that OVO occupies the 2nd place with the highest market penetration and the most promotions, OVO has the lowest rating on the Google Playstore of 4.0. when compared to other fintech applications. Based on data from the Google Playstore, the OVO application has experienced a decrease in rating due to frequent errors, so many users have submitted complaints to reviews on Google Playstore, such as OVO user complaints regarding transaction limits, feature limitations, slow performance of the OVO application. Complaints submitted by OVO users tend to point to the quality of service and systems in the OVO application. Even though the higher the quality of the services provided will significantly affect the level of user satisfaction. In this study, an evaluation was carried out using the SUS method, namely to measure the feasibility level of the application on the user's side so that the application can be useful and can properly address user needs. And based on testing the data that has been processed, the average usability value of the OVO application gets a score of 69.23. This score shows that the OVO application has a usability level already in the OK category where the average usability value of the OVO application is more than equal to 68, which means that it is still generally acceptable but with several improvements such as increasing the use of better features so that it runs smoothly. properly and improve the appearance of the user interface which is easier to understand and use for new users so that it increases good usability in using the OVO application